Chemical Analysis of Essential Oils from Turmeric (Curcuma longa) Rhizome Through GC-MS - Naz, Shagufta; Ilyas, Saiqa; Parveen, Zahida; Javed, Sumera (Asian Journal of Chemistry, 2010)
The volatile oil of turmeric (Curcuma longa L., zingiberaceae) was isolated from its rhizomes. Gas chromatography-mass spectrometry (GC-MS) was applied to the methanolic extract of C. longa. The chromatographic analysis of oil showed 16 constituents of which, 6 compounds contributing 70.0 % of the total oil constituents could be identified. The compounds were identified on the basis of their fragmentation pattern and matching with the data library. The most abundant components were aromatic turmerone (25.3 %), α-tumerone (18.3 %) and curlone (12.5 %). Other constituents are caryophyllene (2.26 %) and eucalyptol (1.60 %). The component present in lowest amount is α-phellandrene (0.42 %).